Effects of rice protein coatings combined or not with propolis on shelf life of eggs. (30th April 2019) - Pires, P G S; Pires, P D S; Cardinal, K M; Leuven, A F R; Kindlein, L; Andretta, I
ABSTRACT: Although eggs are an excellent protein source, they are a perishable product. Many methods exist to extend shelf life of food and one of them is the use of protein coatings that may be combined with antimicrobial substances, as propolis. The effectiveness of rice protein coatings plus propolis on maintaining interior quality and eggshell breaking strength of fresh eggs was evaluated during storage at 20°C for 6 wk. Egg quality was assessed by weight loss, Haugh unit (HU ), albumen pH, yolk index (YI ), shell strength, and scanning electron microscopy in uncoated eggs (control treatment) and eggs coated with rice protein concentrate and propolis at 5 or 10%. The HU and YI were higher in coated eggs ( P < 0.001). Weight loss increased ( P < 0.001) during long-term storage. Uncoated eggs showed the highest weight loss (5.39%), whereas rice protein (4.27%) and rice protein plus propolis at 5% (4.11%) and 10% (4.40%) solutions were effective in preventing weight lost ( P < 0.001). Uncoated eggs had the worst ( P < 0.001) HU (58.47), albumen pH (9.48), and YI (0.33) after 6 wk of storage. The eggs coated with rice protein and rice protein plus propolis presented results with similar intern quality between them during all the storage period. Scanning electron microscopy demonstrated a lower surface porosity in coated eggshell, indicating that the use of the coating may provide a protective barrier against the transfer of gases and moisture. In conclusion rice protein and propolis treatments helped to maintain egg quality for a longer time compared to uncoated eggs. These could be a viable alternative for maintaining the internal quality of fresh eggs during long-term storage at room temperature.